TRIPLE-DIVIDENDS: TOWARD PIGOVIAN GASOLINE TAXATION (Utah Environmental Law Review, 2010)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} The American public's demand for inexpensive gasoline and indifference to the risks posed by climate change have shaped the nation's traditional and alternative energy policies. Public opinion encourages lawmakers to implement inconsistent and economically inefficient policies, which not only fail to satisfy the nation's energy needs but produce a host of secondary economic, national security, and environmental problems. This article advocates replacing the United States' current panoply of ineffective government subsidies and mandates with an efficient, market-driven solution: higher federal gasoline taxes. Whereas previous environmental tax proposals assume constant tax revenue, this article considers the potential to reduce costly foreign policy expenditures in light of decreased domestic petroleum demand. This broader view suggests that Pigovian gasoline taxes would yield triple-dividends, simultaneously benefiting the United States' economy, national security outlook, and environment. Recognizing the incentives responsible for current energy policies provides insight into how higher federal gasoline taxes might successfully be promoted and enacted.